THE EFFECT OF SCHOOL PRINCIPAL SUPERVISION, SCHOOL ORGANIZATIONAL CULTURE AND TEACHER'S SELF-EFFICIENCY ON TEACHER PERFORMANCE AT SMK NEGERI TENGGARONG KOTA - Laili Komariyah; Usfandi Haryaka; Titik Wulandari (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This study aims to determine the effect of Principal Supervision, School Organizational Culture and Teacher Self-Efficacy on Teacher Performance at SMK Negeri Tenggarong Kota. The population of this study was all teachers consisting of three different schools, namely SMKN 1, SMKN 2 and SMKN 3 Tenggarong with a total sample of 110 teachers who were taken using stratified proportional random sampling technique. The data collection technique was carried out using a questionnaire to obtain data on the supervision of the principal, school organizational culture, teacher self-efficacy and teacher performance. Data analysis with instrument validation of the four variables, namely using Pearson correlation and reliability using Cronbach alpha, while for the research approach using multiple linear regression analysis. The results showed that (1) the principal's supervision had a significant effect on teacher performance, which means that the higher the principal's supervision would lead to an increase in teacher performance (2) the school's organizational culture had a significant effect on teacher performance, which means that the better the school's organizational culture, the higher teacher performance (3) teacher self-efficacy has a significant effect on teacher performance, which means the better teacher self-efficacy will result in increased teacher performance (4) principal supervision, school organizational culture and teacher self-efficacy together have a significant effect on teacher performance. Based on the results of the study, it can be concluded that the performance of State Vocational School teachers in Tenggarong City can be improved by the supervision of the principal, school organizational culture and teacher self-efficacy.